Pemberdayaan Masyarakat melalui Digitalisasi Usaha, Optimalisasi Pekarangan, dan Penguatan Layanan Sosial di Dusun Nglengis - Veronika Marosa Kabut; Tulus Fajar Pangestu; Retno Kurnianingsih; Jesinta Kotilda Dinda (Mafapress Institut Pesantren Mathali'ul Falah Pati, 2026)
This community service activity was conducted in Dusun Nglengis through the Community Service Program under the guidance of one field supervisor and involved ten students. The activity aimed to support the community through business strengthening, home yard utilization, assistance in Quran learning activities, and support for posyandu services. The method used was Participatory Action Research through observation, joint planning with residents, program implementation, and evaluation. The participants included four small business owners, nine housewives managing home yards, fourteen active Quran learning students, and three posyandu cadres. The results showed that all targeted small businesses were successfully registered on Google Maps and provided with business banners, two simple planting models using used gallon containers were created, attendance in Quran learning activities increased from an average of eight to fourteen children per meeting, and posyandu services became more organized. This activity shows that simple programs designed from community needs can help strengthen the social and economic capacity of local residents.